2011
DOI: 10.1113/expphysiol.2011.059907
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and sympathetic nerve contributions to the cutaneous vasodilator response from a noxious heat stimulus

Abstract: We investigated the roles of sensory and noradrenergic sympathetic nerves on the cutaneous vasodilator response to a localized noxious heating stimulus. In two separate studies, four forearm skin sites were instrumented with microdialysis fibres, local heaters and laser-Doppler probes. Skin sites were locally heated from 33 to 42• C or rapidly to 44 • C (noxious). In the first study, we tested sensory nerve involvement using EMLA cream. Treatments were as follows: (1) control 42• C; (2) EMLA 42 • C; (3) contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 47 publications
(73 reference statements)
7
59
0
2
Order By: Relevance
“…One site on the forearm and one site on the leg were randomly chosen to receive the topical EMLA cream treatment (AstraZeneca, Wilmington DE, USA; 2.5 % lidocaine and 2.5 % prilocaine). As per our previous experiments blocking cutaneous sensory function with EMLA cream (Tew et al 2011a;Carter and Hodges 2011;Hodges et al 2007Hodges et al , 2009), approximately 2.5 g of the EMLA cream was applied on the forearm to an area of the skin roughly equal to 4 cm 2 . An occlusive dressing (Tegaderm, 3 M, London, ON, Canada) was placed over the applied EMLA cream and left for 1 h. The EMLA cream was then wiped clear and a second application was applied for an additional hour.…”
Section: Instrumentation and Experimental Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…One site on the forearm and one site on the leg were randomly chosen to receive the topical EMLA cream treatment (AstraZeneca, Wilmington DE, USA; 2.5 % lidocaine and 2.5 % prilocaine). As per our previous experiments blocking cutaneous sensory function with EMLA cream (Tew et al 2011a;Carter and Hodges 2011;Hodges et al 2007Hodges et al , 2009), approximately 2.5 g of the EMLA cream was applied on the forearm to an area of the skin roughly equal to 4 cm 2 . An occlusive dressing (Tegaderm, 3 M, London, ON, Canada) was placed over the applied EMLA cream and left for 1 h. The EMLA cream was then wiped clear and a second application was applied for an additional hour.…”
Section: Instrumentation and Experimental Proceduresmentioning
confidence: 99%
“…During this time the second EMLA application was applied on the leg. Finally, T loc on the forearm sites was increased to 44 °C at 1 °C min −1 (2 min in total) and held at this temperature for 20 min to achieve maximal vasodilatation (Tew et al 2011a;Carter and Hodges 2011;Vionnet et al 2014;Lawley et al 2014). After this, forearm data collection sensory nerve blockade was again verified.…”
Section: Instrumentation and Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Kellogg et al [129] showed that even a small sense of pain caused the vasodilation to remain even in the presence of nitric oxide synthase inhibitors, indicating other involving mechanisms. Carter and Hodges [130] reported an absence of initial peak and nadir when heating the skin rapidly to 44°C, where all subjects reported a short period of mild pain. Even if none of the participants in the studies in paper IV and V reported a sense of pain, a first peak and nadir were absent in several subjects in paper V. This indicates that the chosen temperature of 44°C in the study had probably caused minor pain and a temperature of <41°C is probably a better choice in future studies.…”
Section: Clinical Applications and Future Researchmentioning
confidence: 96%